Beam to Chart: A Case Study of the LIDAR Survey of the Sound of Harris - Wakefield, Martin; Sinclair, Mark; Townsend, Nigel (The International Hydrographic Review, 2006)
Tenix LADS Corporation conducted the LIDAR survey of the Sound of Harris in March 2004, for the Maritime and Coastguard Agency (MCA). The survey was conducted using the LADS Mk II system. The survey area was most complex with many islands, shoals and narrow channels (see Figure 1). Survey data extended from topographic heights up to 50 metres above the sea surface to maximum depths of 25 metres below chart datum.